2016
DOI: 10.1093/europace/euw206
|View full text |Cite
|
Sign up to set email alerts
|

Brugada syndrome in the young: an assessment of risk factors predicting future events

Abstract: Symptomatic BS in the young age is a rare but malignant condition that can manifest with a spectrum of electrical abnormalities (i.e. SND, atrial tachycardias, AV block, and infra-nodal conduction delay) and result in the extreme cases in lethal arrhythmic events and SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
1
41
1
1
Order By: Relevance
“…Five studies reported the mean ± SD of PR interval in groups with and without major arrhythmic events. Corcia et al (2 studies) and Morita et al showed a longer PR interval in patients with major arrhythmic events . Juntilla et al, Ohkubo et al, and Corcia et al demonstrated that although the mean PR interval seemed to be higher, there was no significant difference in mean PR interval in Brugada syndrome patients with or without major arrhythmic events .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Five studies reported the mean ± SD of PR interval in groups with and without major arrhythmic events. Corcia et al (2 studies) and Morita et al showed a longer PR interval in patients with major arrhythmic events . Juntilla et al, Ohkubo et al, and Corcia et al demonstrated that although the mean PR interval seemed to be higher, there was no significant difference in mean PR interval in Brugada syndrome patients with or without major arrhythmic events .…”
Section: Resultsmentioning
confidence: 96%
“…We included 7 studies (6 cohorts and 1 case‐control) for qualitative synthesis (Table ), and 7 studies were available for meta‐analysis. We included 1526 subjects from 7 studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other ECG abnormalities such as QRS fragmentation, prolonged QRS duration, T peak-T end interval (transmural dispersion of repolarization), presence of wide S wave in lead I, and prominent R wave in aVR are associated with an elevated risk of arrhythmias [20,21]. Moreover, in a prospective cohort study of young patients with BrS, it was shown that the presence of first degree atrioventricular block (AVB), atrial arrhythmias, sick sinus node disease, and spontaneous type 1 BrS ECG pattern were indicators of future ventricular arrhythmias [22]. Taking into account the high incidence of different cardiac rhythm abnormalities in BrS, including atrial fibrillation, the most common atrial arrhythmia in BrS (incidence ranging from 6% to 53%), active screening and timely introduction of proper management is appropriate in this group of patients [23][24][25].…”
Section: Risk Assessment In Brugada Syndromementioning
confidence: 99%